2020
DOI: 10.4314/ijbcs.v14i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local hot smoking on proximate composition, lipid oxidation, fatty acid profile and minerals content of <I>Chrysichthys nigrodigitatus</I> from Lake Maga in Cameroon

Abstract: Fish with higher nutrient qualities can be used to solve malnutrition problems in Africa. So the aim of this study was to evaluate the effect of local smoking on proximate composition and lipid oxidation of Chrysichthys nigrodigitatus collected in Cameroon. The proximate composition was assessed using standard methods while lipid quality assessment was based on the determination of biochemical indexes. A change on fatty acid composition was evaluated by gas chromatography while minerals composition was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Smoking and boiling decreased significantly (P < 0.05) water content of C. carpio, Arius parkii and E. fimbriata compared to fresh fish. Similar results were observed by Tenyang et al [ 39 ] who showed that the water content of Chrysichthys nigrodigitatus decreased during smoking and boiling. According to Nsoga et al [ 40 ] fish lose about 20% of their initial weight during heat treatments such as smoking.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Smoking and boiling decreased significantly (P < 0.05) water content of C. carpio, Arius parkii and E. fimbriata compared to fresh fish. Similar results were observed by Tenyang et al [ 39 ] who showed that the water content of Chrysichthys nigrodigitatus decreased during smoking and boiling. According to Nsoga et al [ 40 ] fish lose about 20% of their initial weight during heat treatments such as smoking.…”
Section: Resultssupporting
confidence: 90%
“…Smoking increased significantly (P < 0.05) lipid content in all three species. Tenyang et al [ 39 ] showed that lipid content increases during smoking. Indeed, dehydration due to heat treatments such as smoking would increase lipid content .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations